2020
DOI: 10.2196/15717
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pediatric Mobile Game Play on Healthy Eating Behavior: Randomized Controlled Trial

Abstract: Background Video and mobile games have been shown to have a positive impact on behavior change in children. However, the potential impact of game play patterns on outcomes of interest are yet to be understood, especially for games with implicit learning components. Objective This study investigates the immediate impact of fooya!, a pediatric dietary mobile game with implicit learning components, on food choices. It also quantifies children’s heterogeneo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In particular, mHealth interventions have the potential to better engage youth about health-related topics, compared with traditional health interventions [17]. Among youth, mHealth apps have been found to increase fruit and vegetable intake [30][31][32][33], improve nutrition knowledge [32][33][34], promote food choice awareness and healthy eating behaviors [35,36], reduce sugar intake [37], and improve physical activity [38]. Furthermore, mHealth apps, as part of multicomponent interventions, can be effective tools to improve and support health-related behaviors [38].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mHealth interventions have the potential to better engage youth about health-related topics, compared with traditional health interventions [17]. Among youth, mHealth apps have been found to increase fruit and vegetable intake [30][31][32][33], improve nutrition knowledge [32][33][34], promote food choice awareness and healthy eating behaviors [35,36], reduce sugar intake [37], and improve physical activity [38]. Furthermore, mHealth apps, as part of multicomponent interventions, can be effective tools to improve and support health-related behaviors [38].…”
Section: Introductionmentioning
confidence: 99%
“…The games used also vary, some use Foodbot Factory [10], Feed the alien [11], My Plate Picks [12], and Play and grow [13]. Research in the field of nutritional behavior also found that the characters used in the game affect the selection, snack consumption patterns [14], and healthy eating patterns [15]. In addition, games are also effectively used to promote healthy eating patterns in obese children [16], [17].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that health digital platforms can help to improve physical activity, healthy eating, and socialization ( 71 - 74 ). Moreover, mHealth applications demonstrated an effectiveness to treat various behavioral outcomes such as an adherence to the treatment ( 75 - 79 ).…”
Section: Discussionmentioning
confidence: 99%